2004
DOI: 10.1002/iroh.200310643
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Functioning of the “Egg Bank” of a Fairy Shrimp in a Temporary Pool: Chirocephalus ruffoi from Pollino National Park (Southern Italy) as a Case Study

Abstract: To investigate their distribution and total numbers, resting eggs of the anostracan Chirocephalus ruffoi were collected from the bed of a temporary pool in southern Italy. Samples were taken at 0.5 m intervals along six transects oriented at 30°from each other, by means of a cylindrical core sampler. The horizontal distribution of intact resting eggs was extremely patchy, with cyst number per core ranging from 191 to 1,400 (CV = 32.7%), corresponding to a mean of between 0.8 and 4.3 cysts cm -3 . Differences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 69 publications
1
23
2
Order By: Relevance
“…Thiéry, 1997;Brendonck et al, 1998;Mura, 2004Mura, , 2005 and the role of the wind in the dispersal of zooplankton, large branchiopods eggs and other invertebrates (Baujard & Martiny, 1994;Cáceres & Soluk, 2002;Graham & Wirth, 2008 and literature therein). As already reported for phytoplankton, the effectiveness of the dispersal of these animals seems to be linked to the distance among sites.…”
Section: Dispersal By Physical Vectorsmentioning
confidence: 99%
“…Thiéry, 1997;Brendonck et al, 1998;Mura, 2004Mura, , 2005 and the role of the wind in the dispersal of zooplankton, large branchiopods eggs and other invertebrates (Baujard & Martiny, 1994;Cáceres & Soluk, 2002;Graham & Wirth, 2008 and literature therein). As already reported for phytoplankton, the effectiveness of the dispersal of these animals seems to be linked to the distance among sites.…”
Section: Dispersal By Physical Vectorsmentioning
confidence: 99%
“…In spite of this, and in contrast to the plethora of studies on the cyst banks of zooplankters from permanent waterbodies (see review in MARCUS, 1996;MURA, 2004), no information on the structure and functioning of anostracan cyst banks was available until recent years.…”
Section: Introductionmentioning
confidence: 83%
“…The horizontal and vertical distributions of cysts in the pool bed were determined. The comparison between cyst bank estimate (MURA, 2004) and the actual number of cysts counted in the pool bed revealed an estimate error of 20.9%. Resting eggs occurred only in the upper 2.5 cm thick soil sections and decreased within this section as depth increased.…”
mentioning
confidence: 97%
“…Zarattini et al (2002) hatched Chirocephalus diaphanus Prévost, 1803 eggs, but reported that individual egg fractions hatched only after one, two or three hydrations, and each hatching group demonstrated a level of genetic distinction from the other two groups. Mura (2004) found variation in hatching response within individual pools depending upon whether the sediment was moist or dry prior to culture, and recognised that it may be the result of mixed genotypes within the egg bank.…”
Section: Discussionmentioning
confidence: 99%